2020
DOI: 10.1038/s41598-020-58114-3
|View full text |Cite|
|
Sign up to set email alerts
|

Early pregnancy ultrasound measurements and prediction of first trimester pregnancy loss: A logistic model

Abstract: Our objective was to prospectively validate the use of gestational sac (GS), yolk sac (YS) diameter, crown-rump length (CRL), and embryonal heart rate (HR) dimensions to identify early pregnancy loss. This was a prospective cohort study of first trimester pregnancies. GS and YS diameter, CRL, and HR measurements were serially obtained in singleton and twin pregnancies from 6 through 10 weeks’ gestation. Non-parametric tests and logistic regression models were used for comparisons of distributions and testing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…For this reason, the presence of CRL  5 th percentile for GA could predict subsequent miscarriage. Also, Detti et al (8) reported that the deterioration in progressive increase in the CRL signify miscarriage of pregnancies in their group of women, which runs in line with our results. Radwan et al (9) found that there was no significant difference between miscarriage group and ongoing pregnancy group regarding CRL, which is conflicting with our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For this reason, the presence of CRL  5 th percentile for GA could predict subsequent miscarriage. Also, Detti et al (8) reported that the deterioration in progressive increase in the CRL signify miscarriage of pregnancies in their group of women, which runs in line with our results. Radwan et al (9) found that there was no significant difference between miscarriage group and ongoing pregnancy group regarding CRL, which is conflicting with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Our study results agree‫س‬ with Detti et al (8) who demonstrated that there was no statistical difference regarding maternal age and BMI that signify miscarriage. Also, Radwan et al (9) found that there was no statistical difference regarding maternal age and BMI that signify miscarriage.…”
Section: Discussionsupporting
confidence: 92%
“…Smaller CRL [22,28] and lower fetal heart rate (24,28,29] for gestational age have also been reported in pregnancies that subsequently miscarried whereas in those cases the yolk sac size has been described as normal [24], decreased [29] or increased [25,30,31]. The gestational sac and yolk sac sizes starts deviating from normality as early as 6 weeks of gestation followed by changes in CRL and fetal heart rate at 7 and 8 weeks [26]. In the present study, we found a significantly (P <.001) higher incidence of GSD < 5 th centile for gestational age (Table 1) and median gestational sac size (Table 2) in TEPs than in CSPs.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, in women with known last menstrual period in spontaneous pregnancies or known date of ovulation or embryo transfer in pregnancies resulting from ART, a smaller than expected GSD has been reported by all authors as predictive of subsequent miscarriage despite a normal fetal cardiac activity [21][22][23][24][25][26][27]. Smaller CRL [22,28] and lower fetal heart rate (24,28,29] for gestational age have also been reported in pregnancies that subsequently miscarried whereas in those cases the yolk sac size has been described as normal [24], decreased [29] or increased [25,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the distance from the most cephalad to the most caudal extremities to obtain the CRL of the embryo was performed in the maximum long-axis or median sagittal section, with the embryo in a naturally extended position. 10 Routine transabdominal nuchal translucency tests were performed on women who met the criteria for nuchal translucency screening (CRL ≥ 45 mm).…”
Section: Materials S and Me Thodsmentioning
confidence: 99%